2021
DOI: 10.1016/j.nbscr.2021.100065
|View full text |Cite
|
Sign up to set email alerts
|

A population-based prospective study on rest-activity rhythm and mild cognitive impairment among Hong Kong healthy community-dwelling older adults

Abstract: Background Relatively few studies investigated the association between rest-activity circadian rhythm and cognitive impairment in population-based study, and the evidence from Asian populations is sparse. We aimed to examine the relationship of actigraphy measured rest-activity circadian rhythm with mild cognitive impairment (MCI) or cognitive impairment in Hong Kong healthy community-dwelling older adults. Methods We recruited 174 Hong Kong healthy adults aged ≥65 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…with patients with MCI. [58] Several recent studies have also confirmed that advanced acrophase (representing the rest-activity phase and timing of peak activity) and increased activity fragmentation, as reflected by increased intra-daily variability, are the most consistent alterations in MCI relative to age-matched healthy comparison groups. [23,35,59]…”
Section: Review and Metaanalysismentioning
confidence: 81%
See 2 more Smart Citations
“…with patients with MCI. [58] Several recent studies have also confirmed that advanced acrophase (representing the rest-activity phase and timing of peak activity) and increased activity fragmentation, as reflected by increased intra-daily variability, are the most consistent alterations in MCI relative to age-matched healthy comparison groups. [23,35,59]…”
Section: Review and Metaanalysismentioning
confidence: 81%
“…[ 56 ] Patients with MCI have also greater nighttime activity and less activity in the morning compared to aged matched controls (Figure 1b); [ 57 ] although, one study found no differences in circadian phase or rest‐activity patterns in cognitively intact older adults compared with patients with MCI. [ 58 ] Several recent studies have also confirmed that advanced acrophase (representing the rest‐activity phase and timing of peak activity) and increased activity fragmentation, as reflected by increased intra‐daily variability, are the most consistent alterations in MCI relative to age‐matched healthy comparison groups. [ 23,35,59 ]…”
Section: Circadian Rhythm Changes In Healthy Aging and MCImentioning
confidence: 92%
See 1 more Smart Citation
“… Oosterman et al (2009) and Yang et al (2022) also found that weaker CRARs (i.e., lower amplitude and relative amplitude) were associated with poorer performance on tests of memory, executive function, auditory attention, and global cognition. Yi Lee et al (2021) , however, found no association of rhythm strength metrics (i.e., mesor, amplitude) or circadian timing (i.e., acrophase) with dementia or MCI status at baseline. Longitudinal studies examining CRARs with subsequent change in cognitive performance have found that metrics indicative of lower rhythm strength (i.e., mesor, amplitude) and delayed rhythm timing (i.e., later acrophase) were associated with greater declines in global cognition and executive function ( Walsh et al, 2014 ; Rogers-Soeder et al, 2018 ; Yi Lee et al, 2021 ; Xiao et al, 2022a , b ), and increased risk for MCI and dementia ( Xiao et al, 2022b ).…”
Section: Introductionmentioning
confidence: 79%
“… Yi Lee et al (2021) , however, found no association of rhythm strength metrics (i.e., mesor, amplitude) or circadian timing (i.e., acrophase) with dementia or MCI status at baseline. Longitudinal studies examining CRARs with subsequent change in cognitive performance have found that metrics indicative of lower rhythm strength (i.e., mesor, amplitude) and delayed rhythm timing (i.e., later acrophase) were associated with greater declines in global cognition and executive function ( Walsh et al, 2014 ; Rogers-Soeder et al, 2018 ; Yi Lee et al, 2021 ; Xiao et al, 2022a , b ), and increased risk for MCI and dementia ( Xiao et al, 2022b ). Other work has shown that greater IV at baseline and greater increases in IV were associated with greater declines in global cognition, and that lower RA and IS, and higher IV at baseline was associated with greater risk for developing incident cognitive impairments among older adult men ( Xiao et al, 2022a ).…”
Section: Introductionmentioning
confidence: 79%